Penerapan Model Project Based Learning Meningkatkan Kreativitas dan Hasil Belajar Muatan Pelajaran IPS - Puji Astuti; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
This research is motivated by observational data which shows that the results of observations and the acquisition of social studies learning outcomes are low. Student creativity in social studies learning is channeled as it should be. The average value of social studies learning outcomes has not reached the KKM. One of the efforts to overcome this is by applying a problem-based learning model. This study aims to determine the application of the Project-Based Learning model in increasing creativity and learning outcomes of social studies lessons for fourth-grade students at SD Negeri Melikan. The methodology used in this research is Classroom Action Research (CAR). The subjects were 11 students from the fourth-level SD Negeri Melikan. Data were collected utilizing observation, document analysis, and tests. The data analysis used is a descriptive analysis technique with qualitative and quantitative approaches. The research process is carried out in two cycles and each cycle includes four stages, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. The results show that creativity and learning outcomes can be increased through the Project-Based Learning model. Students with creativity good category from pre-cycle 5 students (45.45%) to 7 students (63.63%) in the first cycle and 10 students (90.9%) in the second cycle. Social studies learning outcomes increased from the average an average of 68.64 in the pre-cycle to an average of 74.54 in the first cycle and an average of 80.9 in the second cycle. This study concludes that the application of the Project-Based Learning Model can improve creativity and learning outcomes for social studies lessons for grade IV at SDN Melikan Rongkop Gunungkidul in the 2021/2022 academic year.